Multi-level ROS regulation to activate innate and adaptive immune therapies - Feng, Ke-Ke; Li, Cheng-Lei; Tu, Yi-Fan; Tian, Shi-Cheng; Xiong, Rui; Sa, Bai-Sheng; Shao, Jing-Wei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
•VGRM integrated GOx and CRISPR/Cas9 on 2D vanadium carbide MXene for enhanced ROS and immune activation.•VGRM amplified ROS production and depleted GSH via cascade reaction, enhancing tumor cell damage.•VGRM activated cGAS/STING pathway, induced ICD, promoted CD8+ T cell infiltration, and reversed immunosuppression.•VGRM had excellent NIR-II photothermal performance for photoacoustic imaging and photothermal therapy.•VGRM inhibited tumor growth, recurrence and metastasis via ROS, photothermal, and immune activation. Reprogramming the immunosuppressive tumor microenvironment (TME) to boost CD8+ T cell infiltration is crucial for anti-tumor immunotherapy. In this study, a bionic nanoplatform (VGRM) based on a two-dimensional vanadium carbide (MXene) carrying glucose oxidase (GOx) and CRISPR/Cas9 was constructed, which enabled a cascade reaction that amplified the generation of reactive oxygen species (ROS) while depleting glutathione (GSH) by combining MXenzyme and natural enzymes. The CRISPR/Cas9 system could reduce the expression of MTH1, depress tumor cells’ self-defense against oxidative stress and thus significantly enhance the therapeutic effect of ROS. Additionally, the excellent NIR-II photothermal performance endowed VGRM with photoacoustic imaging (PA) and photothermal therapy (PTT) capabilities. The enhanced oxidative stress and photothermal killing ability could activate the cGAS/STING innate immune pathway, induce immunogenic cell death (ICD), and at the same time reverse the immunosuppressive TME, which promoted CD8+ T cells infiltration, and thereby inhibiting tumor proliferation. Meanwhile, antigen-activated memory T cells (adaptive immunity) could suppress tumor recurrence and metastasis effectively. This study provides a novel strategy for the combined application of MXene and gene editing therapy in modulating the tumor immune microenvironment.